ANN-Based Control of a Wheeled Inverted Pendulum System Using an Extended DBD Learning Algorithm. (24th May 2016) - Cruz, David; García, Salatiel; Bandala, Manuel
This paper presents a dynamic model for a self-balancing vehicle using the Euler-Lagrange approach. The design and deployment of an artificial neuronal network (ANN) in a closed-loop control is described. The ANN is characterized by integration of the extended delta-bar-delta algorithm (DBD), which accelerates the adjustment of synaptic weights. The results of the control strategy in the dynamic model of the robot are also presented.